BENZYLTRIMETHYLAMMONIUM CHLORIDE IMMERSION EFFECT ON PHYSICAL PROPERTIES OF TiO2 – Al203 - Silvester Tursiloadi; Hiroshi Hirashima (Jurnal Sains Materi Indonesia, 2004)
BENZYLTRIMETHYLAMMONIUM CHLORIDE IMMERSION EFFECT ON PHYSICAL PROPERTIES OF TiO2 – Al2O3. Mesoporous TiO2 - Al2O3 powders have potential applications in catalysts or support catalysts. A novel method to control pore size of sol--gel by a cationic surfactant benzyltrimethylammonium chloride (BTAC) Immersion was investigated. The gels of TiO2- Al2O3 in molar ratio of 0.2 of TiO2, and 0.8 of Al2O3 were prepared by hydrolysis of aluminium sec-butoxide, Al(OC4H9sec)3 and titanium isopropoxide Ti(OC3H7iso)4 in an n-propanol solution with acid catalyst. The structures and porosities of the modified TiO2-A|2O3 was depended on the dimensions of surfactant, as long as the calcination was carried out at 500℃ to avoid aggregation process during removal of excess BTAC. If the calcinations were carried out at 800℃ no significant change of the pore volume of modified samples was remarkably not observed, even though formation of TiO2 rutile has been taken place. It indicated that samples modiﬁcation by initial immersion of gel into BTAC may avoid the sintering. These results suggest that during the calcinations TiO2, was segregated from the Al2O3 particles to form nuclei of rutile and was crystallized prior to formation of α- Al2O3. Therefore, the formation of rutile TiO2 induced the formation of α- Al2O3.